Responsiveness of intestinal epithelial cell lines to lipopolysaccharide is correlated with Toll-like receptor 4 but not Toll-like receptor 2 or CD14 expression - Böcker, Ulrich; Yezerskyy, Oleksandr; Feick, Peter; Manigold, Tobias; Panja, Asit; Kalina, Uwe; Herweck, Frank; Rossol, Siegbert; Singer, Manfred V. (International journal of colorectal disease, 2003)
Abstract